ANALISIS MAKNA DENOTATIF DAN KONOTATIF DALAM PANTUN PENOBATAN GELAR DATUK DI KUANTANSINGINGI: KAJIAN SEMANTIK - Sri Rahayu; Selsi Aulia; Ririn Rahmadani; Dani Arli Ramayani; Alfa Ramadandika; Tasya Ayuni Syahira; Dhea Altha Fino; Suci Ramadhani (JURNAL SELAKSA MAKNA, 2026)
Language is the primary means of communication and the transmission of local wisdom, especially in Malay society, which is rich in oral literary traditions such as pantun. The problem of this research is how the denotative and connotative meanings in the pantun for the coronation of the Datuk title in Kuantan Singingi. This study aims to describe and analyze both types of meanings. The method used is descriptive qualitative with data sources in the form of pantun texts resulting from interviews with native Kuantan Singingi residents who understand the traditional procession. Data collection techniques were carried out through interviews, listening, and taking notes, while data analysis used Abdul Chaer's semantic theory which focuses on the relationship between language forms and denotative and connotative meanings. The results of the study show that there are 16 data in eight pantun stanzas consisting of 8 denotative meanings and 8 connotative meanings. This is because each stanza is composed of a sampiran and a fixed pattern of content, where the sampiran describes concrete things that have denotative meanings and the content contains traditional messages that have connotative meanings. This balance occurs because, in the Malay tradition, pantun serves as both a medium for conveying messages and a linguistic aesthetic that demands harmony between form and meaning. This uniqueness lies in the balance between literal and symbolic meaning in each verse of the pantun conferring the title of Datuk in Kuantan Singingi.   Bahasa merupakan sarana utama komunikasi dan pewarisan kearifan lokal, terutama dalam masyarakat Melayu yang kaya akan tradisi sastra lisan seperti pantun. Permasalahan penelitian ini adalah bagaimana makna denotatif dan konotatif dalam pantun penobatan gelar Datuk di Kuantan Singingi. Penelitian ini bertujuan untuk mendeskripsikan dan menganalisis kedua jenis makna tersebut. Metode yang digunakan adalah deskriptif kualitatif dengan sumber data berupa teks pantun hasil wawancara dengan masyarakat asli Kuantan Singingi yang memahami prosesi adat. Teknik pengumpulan data dilakukan melalui wawancara, simak, dan catat, sedangkan analisis data menggunakan teori semantik Abdul Chaer yang berfokus pada hubungan bentuk bahasa dengan makna denotatif dan konotatif. Hasil penelitian menunjukkan terdapat 16 data dalam delapan bait pantun yang terdiri atas 8 makna denotatif dan 8 makna konotatif. Hal ini karena setiap bait tersusun atas sampiran dan isi yang berpola tetap, di mana sampiran menggambarkan hal konkret yang bermakna denotatif dan isi memuat pesan adat yang bermakna konotatif. Keseimbangan ini terjadi karena dalam tradisi Melayu pantun berfungsi sebagai media penyampaian pesan sekaligus estetika bahasa yang menuntut keselarasan bentuk dan makna. Inilah keunikannya, yaitu adanya keseimbangan antara makna literal dan simbolik dalam setiap bait pantun penobatan gelar Datuk di Kuantan Singingi.